Analysis of Leading Sector Identification in East Java Province in 2016 (Input-Output Aproach) - Tias, Vriska Ayuning; Sofiani, Fatma; Nida, Lumdah Faridatun; Sabrina, Aisyah Fitri (Bulletin of Islamic Economics, 2024)
In planning alternative strategies, there are a variety of analytical tools that can be used, each with its own advantages and limitations. For example, indicators of prosperity are usually measured through Gross Regional Domestic Product (GRDP). Although GRDP provides an overview of the contribution of each sector to the regional economy, this data is proportional (share) and is not able to describe the relationship between sectors as a whole. In other words, GRDP cannot show the extent of inter-sectoral linkages as the main driver of the regional economy. Therefore, this study uses input-output analysis. This analysis is considered more comprehensive because it is able to describe the linkages between economic sectors in a region as a whole. Through this approach, the impact of production changes in one sector on other sectors can be known more clearly. In addition, input-output analysis can also measure the impact on community welfare through primary inputs in the form of added value. Thus, changes in production in certain sectors can show how much the prosperity of the people in the region has increased or decreased.